COST PLUS PRICING METHOD IN DETERMINING THE SELLING PRICE OF THE BANANA CHIPS (Study at UD. Anisa Jaya Gogodeso Village) - Istika Risyanti; Endah Masrunik (Universitas Islam Balitar, 2018)
UD. Anisa Jaya is located on Arjuno Street Rt 02 Rw.07, Gogodeso Dusun Ngade, Kanigoro Sub-District, Blitar District. This business produces various kinds of products such as banana chips, kardol and others. The researcher focused on banana chips. The aim of the study was to find out the determination of the selling price of banana chips at UD. Anisa Jaya with company methods and cost plus pricing methods. This type of research is quantitative. The data used are primary data and secondary data. From the results of interviews and observations, researchers found the data needed to complete the needed data. Secondary data in the form of organizational structures, documents and business profiles. The results of the study indicate that the selling price set by the company is lower than IDR 1,567 rather than the cost plus pricing method. With the method of selling the selling price used is Rp. 8,000 per pack while the cost plus pricing method is Rp. 9,567. This is because the company does not include all factory overhead costs used in calculating the cost of production while the researcher includes all factory overhead costs in its calculations.